TEACHING ENGLISH IN SEMIOTICS - Muhammad Natsir (BAHAS, 2016)
This paper deals with teaching english in semiotics and their sample applications in the language classroom. The foundation for semiotics must be laid with perception. The objects of perception are percepts. Percepts are not the material objects in the physical realm that the mind imagines (rightly or wrongly) that it is sensing. Visual percepts are patterns of area (shape, size, and position) and color over a two-dimensional field. Audial percepts are patterns of pitch and volume over time. The verbal and the non-verbal aspects of language teaching should not be kept separate. The use of signs, symbols and visual aids by the teachers help the enhancement of the learning capacity of the language learner both at cognitive and meta-cognitive levels as they listen and try to learn a foreign language component in the classroom. Key Words : Semiotics, language teaching methods, context, sign, symbol